Empirical test of a conceptual model to find relevant PPC procedures to strategic entrepreneurship - Silva, J. (RENT XXIII - Research in Entrepreneurship & Small Business, 2009)
This paper addressed the structural change of a SME, focusing on finding relevant Production Planning and Control (PPC) procedures to the case situation. Thus, the utilisation of a previously developed audit tool was reported as a credible way to discuss change alternatives within the strategic scope of the organisational development of the firm. Moreover, despite the credibility of the audit tool had already been established by its theoretical validation according to the Soft Systems Methodology (SSM), there still was a requirement for checking its usefulness. This was the target of the empirical test that will now be presented. The main contribution to the literature was the divulgation of a credible diagnostic tool for developing understanding about the relevance of the PPC procedures within the scope of the Case Study Company (ICSC) under the soft systems guidance. In fact, the usefulness of the developed conceptual model that was reported, confirmed the interest of a rival approach to auditing that is made up of a substantially different nature from the one used by consultants. This empirical test followed the stage 5 of SSM concerning the comparison between the model and the perceived reality from the case. Thus, the previously developed conceptual model – made up of a framework and three propositions – provided a systematic base for ordered questioning. This was achieved by supplying the questions to ask concerning the existing situation, as a source of debate about potential change. The exercise provided room for a dialectical discussion from which changes to the perceptions of the problem situation came out. This was the path to identify relevant PPC procedures to the specific situation of the ICSC and to check the interest of the conceptual model as a useful process of enquiry. The determinants of the organisational structure of TIM Lda (the ICSC) were analysed taking into consideration the recommendations concerning the conceptual positioning of PPC and the organisational structure effectiveness, i.e. both its congruence and conceptual consistency. As a consequence, a top-down analysis attempted to show the impact of the current state of the TIM determinants on the relevant parameters of the definition of its manufacturing system, viz. on PPC. As further work, it was recommended that the approach should be reversed, i.e. a bottom-up analysis based on the design parameters of the manufacturing system should cross-check the previous top-down findings. Finally, two different types of structures were found adequate to fulfill the needs of the two clusters of SBUs, first put together according to the diversity, complexity, stability and hostility of the market. These clusters were also confirmed by the type of technical system, 2 by the age & size of firm, by the use of AMTs and by the longitudinal progress of the workcoordinating mechanisms across time. Moreover, the currently used technology was also found easily divisible. In addition, relevant external pressure to implement formal performance assessment schemes was anticipated. These assessment frameworks were found to be set on the top of formal systems such as PPC and Quality Control. Furthermore, any implementation effort targeting these control procedures was found to require the operational support of IT and the development of a strategically favourable environment to IS progress. To sum up, most of the learning and discussion with regard to the reviewing of the ICSC structure would have been lost, if only rival PPC best practice approaches had been followed, under a reductionist approach. So, the pursuing of a situational, holistic and structured validated approach in order to help a small organisation to follow a strong entrepreneurial strategy seemed useful and significant.